Performance of sweet potato varieties in hilly area (Bangladesh Agronomy Journal, 2015)
The experiment was conducted at the research field of Hill Tract Agricultural Research Station. Ramgarh, Khagrachari during Rabi season of 2012-2013 and 2013-14. Five different sweet potato varieties (BARI Sweetpotato-6, BARI Sweetpotato-7, BARI Sweetpotato-8, BARI Swwetpotato-9 and local cultivar were included as treatment variables in the experiment. BARI Sweetpotato-7 had significantly more number of vines (8.30) as compared to local cultivar and other new varieties such as BARI Sweetpotato-6, BARI Sweetpotato-8 and BARI Sweetpotato-9. Maximum number of tuber plant-1 (5.4 and 5.3), tuber length (15.30 and 15.80 cm), tuber diameter (5.10 and 5.20 cm), individual tuber weight (368.35 and 377.69 g) and tuber yield (19.89 and 20.13 t ha-1) was recorded from BARI Sweetpotato-9 during 2012-13 and 2013-14, respectively whereas local cultivar gave minimum values. The variety BARI Sweetpotato-9 out yielded local cultivar by 108.93 and 103.13 % during two consecutive years but  highest net income (3,10,818 and 3, 15,617 Tk. ha-1) from  BARI Sweetpotato-7Bangladesh Agron. J. 2014, 17(2): 83-87